2020
DOI: 10.3168/jds.2019-17009
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Lactose utilization of Streptococcus thermophilus and correlations with β-galactosidase and urease

Abstract: The ability to use lactose is critical for the application of Streptococcus thermophilus in fermented dairy products. Most studies have evaluated the use of lactose of S. thermophilus by measuring lactose utilization, but its correlation with β-galactosidase and urease has rarely been investigated. In this study, 10 strains of S. thermophilus isolated from fermented yak milk exhibited a diversity of β-galactosidase and urease activities, growth, and acid production in de Man, Rogosa, and Sharpe-lactose. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Urease is a complex enzyme whose subunits and accessory proteins are encoded by 11 genes that account for approximately 0.9% of the core genome of the species ( 23 ). S. thermophilus urease activity has been extensively studied because it exerts a delayed effect on milk acidification ( 24 26 ). Urease activity was reported to be correlated with aspartate, glutamine, and arginine biosynthesis and carbon dioxide metabolism ( 10 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urease is a complex enzyme whose subunits and accessory proteins are encoded by 11 genes that account for approximately 0.9% of the core genome of the species ( 23 ). S. thermophilus urease activity has been extensively studied because it exerts a delayed effect on milk acidification ( 24 26 ). Urease activity was reported to be correlated with aspartate, glutamine, and arginine biosynthesis and carbon dioxide metabolism ( 10 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, urease deficiency results in a decreased rate of acidification and bacterial counts in milk ( 15 , 16 ). More recently, it was reported that the urease activity of S. thermophilus showed a significant correlation with the use of lactose and the production of lactic acid and acetaldehyde ( 26 ). We could, therefore, summarize that the positive effect of urease on S. thermophilus metabolism is the result of several factors, including the modulation of the intracellular and extracellular pH, CO 2 , and NH 3 supply to anabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is not limited to soybean takes role in aging, we observed that bacteria formulation might determine the metabolite active compound resulted by fermentation process. For instance, Bi dobacterium bi dum increases the largest surface area, elevate the most brush border enzyme, and give the best improvement to the transport system compared to Lactobacillus bulgaricus, Streptococcus thermophiles, and Lactobacillus acidophilus [29] and produce more active metabolic products than Lactobacillus spp which initiates other signalling mechanism in tissue [27] As the aging process affect integrity, humidity, pH and elsatisity of skin tissue, and ultimately the epidermis gradually becomes thinner [39], [40]. The thinning of epidermis is caused by the rise of Epidermal Fas expression in aging skin that induce Fas-mediated apotosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Lactobacillus bulgaricus produces D-(-)-lactic acid which is physiologically inactive [28]. The digestion of lactose can be enhanced by the presence of Streptococcus thermophiles through the activity of its microbial β-galactosidase [29].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that β‐galactosidase activity showed a significantly positive correlation with the growth of cell densities, the production of lactic acid and titratable acidity. Also, urease activity of S. thermophilus showed a significant correlation with the use of lactose and the production of lactic acid and acetaldehyde 16 . In S. thermophilus , the permeas LacS operates as a lactose/galactose antiporter or as a galactoside/H+ symporter responsible for lactose transport into the cell 17 .…”
Section: Introductionmentioning
confidence: 99%